Editorial to the Special Issue “Space Missions to Small Bodies: Results and Future Activities” - Andrea Longobardo (Universe)
Small bodies (asteroids, comets, and satellites) are the most primitive bodies of our solar system and, for this reason, represent the key to understanding its origin and early evolution [...]